2020
DOI: 10.1158/1541-7786.mcr-19-0588
|View full text |Cite
|
Sign up to set email alerts
|

Combined Exosomal GPC1, CD82, and Serum CA19-9 as Multiplex Targets: A Specific, Sensitive, and Reproducible Detection Panel for the Diagnosis of Pancreatic Cancer

Abstract: Pancreatic cancer is a highly lethal malignancy with poor prognosis due to the lack of early symptoms and resultant late diagnosis. Thus, it is extremely urgent to establish a simple and effective method for the early diagnosis of pancreatic cancer. Although some studies have provided positive evidence for the use of exosomal surface protein glypican-1 (GPC1) as a biomarker for early screening, its clinical application is still controversial. Here, we systematically verified the role of exosomal GPC1 as a pote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 21 publications
0
31
0
2
Order By: Relevance
“…GPC1+ circulating exosomes were regarded as a therapeutic target (34) and could facilitate the early detection of cancer (33). Another study demonstrated that combined detection of exosomal GPC1, exosomal CD82, and serum CA19-9 shows excellent promise as a standard method for pancreatic cancer detection (35). Likewise, P4HA1 is the active catalytic component of prolyl 4-hydroxylase and has been reported to promote tumor progression and metastasis in several cancers (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…GPC1+ circulating exosomes were regarded as a therapeutic target (34) and could facilitate the early detection of cancer (33). Another study demonstrated that combined detection of exosomal GPC1, exosomal CD82, and serum CA19-9 shows excellent promise as a standard method for pancreatic cancer detection (35). Likewise, P4HA1 is the active catalytic component of prolyl 4-hydroxylase and has been reported to promote tumor progression and metastasis in several cancers (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the combined detection of exosomal GPC1, exosomal CD82, and serum CA19-9 shows great promise as a standard method for PC detection. 183 Another study has shown that the determination of S100B and MIA in exosomes may be an alternative to their analysis in serum for the diagnosis and prognosis of melanoma patients. 184 In addition, exosomal cytoskeleton-associated protein 4 (CKAP4), a novel DKK1 receptor, may represent a biomarker for pancreatic cancer.…”
Section: Exosomes In Cancer Diagnostic and Therapeutic Applicationsmentioning
confidence: 99%
“…Therefore, the development of a risk stratification model may help clinicians to design personalized treatment programs for different patients. Previous studies have proposed various risk stratification models for the diagnosis, prognosis, and recurrence of pancreatic cancer, which exhibited better efficiency than the classical TNM stage (43)(44)(45). The rapid development of sequencing techniques has enabled the access to multi-omics data and high-quality clinical information through different databases, such as TCGA, ICGC, and Gene Expression Omnibus (17,46,47).…”
Section: Discussionmentioning
confidence: 99%